2001
DOI: 10.1200/jco.2001.19.20.4074
|View full text |Cite
|
Sign up to set email alerts
|

MSH2 Mutation Carriers Are at Higher Risk of Cancer Than MLH1 Mutation Carriers: A Study of Hereditary Nonpolyposis Colorectal Cancer Families

Abstract: Pending large prospective studies, the extension of the current surveillance program in MSH2 mutation carriers with the inclusion of the urinary tract should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
249
6
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(292 citation statements)
references
References 19 publications
(17 reference statements)
29
249
6
8
Order By: Relevance
“…1) (Aarnio et al, 1999;Abdel-Rahman et al, 2006;Grover et al, 2009;Hampel et al, 2005;Vasen et al, 2007;Vasen et al, 2001b). This risk varies depending both on the affected MMR gene and on the gene loci involved (Plaschke et al, 2004;ten Broeke et al, 2015;Vasen et al, 2001a;Wijnen et al, 2009). To facilitate genetic counselling and clinical practice, an interactive website providing the complete distributions of all cancer types, depending on gene defect, from any age is now available at is available at http://www.lscarisk.org .…”
Section: Lynch Syndromementioning
confidence: 99%
“…1) (Aarnio et al, 1999;Abdel-Rahman et al, 2006;Grover et al, 2009;Hampel et al, 2005;Vasen et al, 2007;Vasen et al, 2001b). This risk varies depending both on the affected MMR gene and on the gene loci involved (Plaschke et al, 2004;ten Broeke et al, 2015;Vasen et al, 2001a;Wijnen et al, 2009). To facilitate genetic counselling and clinical practice, an interactive website providing the complete distributions of all cancer types, depending on gene defect, from any age is now available at is available at http://www.lscarisk.org .…”
Section: Lynch Syndromementioning
confidence: 99%
“…Most studies estimate the risk of colorectal cancer in families with HNPCC syndrome selected according to Amsterdam criteria without correcting for selection bias [4][5][6][7][8][9] . Estimates in these studies range from 0.68 to 0.82, but these values have been shown to be substantially overestimated 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal and endometrial cancers are the cancer types most frequently reported; mutation carriers are at an estimated lifetime risk of up to 70 and 27-71%, respectively [1,12,23,33,34]. In addition, cancers of the ovaries, stomach, small bowel, hepatobiliary tract, ureter, renal pelvis and brain are part of the HNPCC tumour spectrum [35,38].…”
Section: Introductionmentioning
confidence: 99%
“…This phenotypic heterogeneity has been attributed to genetic and allelic heterogeneity and the influence of sex, genetic modifiers and environmental factors [10,13,14,16,18,24,33,37]. Investigations regarding the influence of environmental factors on phenotypic expression in LS mutation carriers have been limited to colorectal cancer risk only, and the cohorts investigated were generally small [10,19,36,37].…”
Section: Introductionmentioning
confidence: 99%